La representación del Holocausto como problema en la historiografía - Bevilacqua, Gilda (Historiografías, 2022)
In this paper, we will investigate the representation of the Holocaust as a theoretical problem in historiography. To present our approach to this issue, we will first develop one of its most significant expressions: the already classic work Probing the Limits of Representation: Nazism and the “Final Solution”, compiled by Saul Friedlander in 1992, and we will analyze the proposals of some of the leading authors who participated in it. Then, we will address what we have called the “problem of the adequacy between event and representation”, and we will establish our position on it. Finally, we will present some of the main conclusions that we derive in relation to the problems studied.